Successive projections algorithm improving the multivariate simultaneous direct spectrophotometric determination of five phenolic compounds in sea water - Di Nezio, Maria Susana (2007)
This paper proposes an analytical method to determine directly and simultaneously five phenolic compounds (4-nitrophenol, 2-nitrophenol, phenol, 2,4,6-trichlorophenol and 4-chlorophenol) in sea water (Ria de Bahía Blanca, Argentine). The advantages of this method is that only requires spectrophotometric measurements (separation steps and derivatization reagents are avoided) and chemometric modelling (PLS and MLR-SPA). The statistical comparison between PLS - a well established multivariate method - and MLR-SPA - a recently presented chemometric modelling - demonstrated better analytical performance for the later one. This fact is indicative of the potentiality of MLR-SPA for solving complex analytical problems.